Taguchi analysis on machinability of Inconel 600 using Copper, Brass, and Copper tungsten electrodes in EDM. (2021) - Pavan, C.; Sateesh, N.; subbiah, Ram
Abstract: Electric Discharge Machining (EDM) is an unconventional machining technique normally used for machining of electrically conductive metals. Inconel 600 belongs to the group of austenite-nickel–chromium based super alloys which are well suitable for service in extreme conditions exposed to pressure and temperature. In this work, Taguchi Analysis on Machinability of Inconel 600 alloy using Copper, Brass, and Copper tungsten electrodes in EDM is performed. The effect of process parameters such as pulse on time, pulse off time, peak current and gap voltage on the performance measures such as material removal rate (MRR) and tool wear rate (TWR) is studied for various electrode materials. Electrode material is selected for the application which is found from optimum input parameters obtained through Taguchi analysis. It has been observed from the analysis, Copper tungsten electrode showed highest MRR of 0.01579 cm 3 /min and lowest TWR of 0.00045 cm 3 /min for machining Inconel 600 alloy.